Knowledge and Attitude about Tuberculosis Disease in the Community - Inggrita Deanisa lawi; Wanti Wanti; Siprianus Singga; Irfan Irfan; Ragu Harming Kristina (Jurnal Ilmiah Permas: Jurnal Ilmiah STIKES Kendal, 2022)
Tuberculosis (TB) cases in 2020 in East Nusa Tenggara Province were 5,126 with the highest TB cases being Kupang City, with 522 cases or prevalence rate = 118 per 100,000 population with a low cure rate. A person's behavior about TB can affect the incidence of TB and its treatment. This study aims to determine the knowledge and attitudes of the people in Kupang City about tuberculosis. This type of research is descriptive research with knowledge and attitude variables. The sample in this study were 100 respondents from the community in Kupang City. Data was collected using a questionnaire in a google form which was shared via Facebook, WhatsApp, and Instagram. The data collected were processed and analyzed descriptively to see the frequency distribution of the research variables. The knowledge of the community in Kupang City about tuberculosis is 90% including the Good category, 8% in the sufficient category and 2% in the less category. The attitude of the people in Kupang City in the treatment and prevention of tuberculosis transmission is mostly in the Good category (99%) and the remaining 1% is in the Less category. Although the knowledge and attitudes of the community are mostly good, there is still a need for counseling about knowledge, especially about the transmission method of TB which will have an impact on community actions in preventing TB and reducing the incidence of TB in the community.